Indigenous Fish Marketing Practices in Nadia District, West Bengal - Suman Dey; S. N. Ojha (Journal of Indian Fisheries Association, 2017)
Fish being a highly perishable food item requires an effective fish marketing system. Improper market facilities and lack of institutional mechanisms restricts the growth of fisheries marketing. Fish marketing practices are mostly indigenous and cost effective. Accordingly, the present study was conducted to document the indigenous fish marketing practices existing in the markets of West Bengal. The information about the indigenous practices was collected through PRA (Participatory Rural Appraisal) tools like observation and semi structured interviews with various fish farmers, wholesalers, retailers, marketing agents. In this paper, indigenous practices carried out in the various fish markets were recorded along with their scientific rationale of being used by the respective stakeholders. Results of the study depict that the practices found to be ethical should be rationalized more effectively and disseminated among various marketing chain actors and at the same time practices which are found to be unethical should be stopped to reduce the unscrupulous means which few people are adopting.